DETERMINANTS OF FEMALE WORKERS ON ECONOMIC GROWTH - Mohammad Ilham Azizi (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2021)
Introduction: This study aims to find out what influences the Provincial Economic Growth in the Java Island if seen from female workers through the some variables, namely life expectancy of female, female's income contributions, and female as professionals.Methods: In this study using secondary data for 8 years from 2011 - 2018. The data analysis method used in this study is panel data regression analysis method. There are independent variables consisting of female's life expectancy, female's income contribution, and female as professionals. While the dependent variable is economic growth.Results: Based on the results of this study, it can be concluded that life expectancy has no significant effect on economic growth. The contribution of female's income has a significant effect on economic growth. Female as professionals has an insignificant effect on economic growth.Conclusion and suggestion: The central or regional government, the ministry of manpower and the ministry of female's empowerment and child protection or related institution to conduct training and human resource development for female by means of development activities in creating employment expansion, improving the quality of productive workforce and increasing the welfare of the workforce.